Comparison of photodynamic therapy efficiency using radiation sources with different wavelengths in the treatment of sinusitis - G. P. Popova; Yu. A. Nakatis; M. A. Rymsha (Biomedical Photonics, 2019)
Inflammatory diseases of the sinuses – one of the most common nosologies in the practice of otorhinolaryngologist; its pathogenesis is well studied, and treatment recommendations are detailed. Following them, however, cannot completely prevent chronic disease or recurrence. Antimicrobial photodynamic therapy is a promising method of treating sinusitis, which has proved its effectiveness, but has not yet been widely used. This work describes our experience in photodynamic therapy with chlorin e6 of chronic sinusitis using a new laser diode-based irradiation source. For patients who had previous sinus surgery an adapter for penetration into the sinus through anastomosis was developed and tested. First group of the patients underwent photodynamic therapy (PDT) according to the conventional scheme, using a laser with a wavelength of 662 nm; while the second one underwent PDT using a 405 nm laser. With daily washing of the nasal sinus, the period of inflammation relief (evaluated by the absence of pathological discharge during washing) amounted to 3.8 full days on average in the first group of patients, compared to 5.4 days on average for the second group. We carried out the comparative analysis of the treatment results based on clinical assessment and radiological evaluation (CT) at the time of discharge from the hospital and 1 month later.